Technological progress and productivity in the Quinoa sector - Juan Cristóbal Birbuet; Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2009)
The main objective of this case study is to analyze the effect that a significant technological innovation in quinoa processing has had on the productivity of companies devoted to this activity and the impact of such an innovation on the growth and organization of the quinoa cluster in Bolivia, and its possible effects on the future. The study will explain how the boost engendered by technological innovation in quinoa processing has triggered a series of events that have allowed the establishment of an ambitious development program. The sector's main companies and producer associations are part of this program, which is called the Quinoa Alliance. The program has become a unique opportunity for agro-industrial development in the Bolivian Altiplano, so far characterized by subsistence agriculture.
Keywords: 330; Quinoa; saponin; unit operation; specific consumption; productivity